Determination of Key Commodities in the Agropolitan Sector of Subang Regency - Mufarrij, Muhammad; Adhini, Novie Putri; Pratama, Rayhan Naufal; Putri, Laura Diana; Muna, Naurah Maysyah; Ayuningtyas, Adelia Rahmadina; Pramono, Widhi Ningrum Pangestu; Rahmawati (Perencanaan Wilayah dan Kota FT UB, 2025)
The development of the agropolitan area in Subang Regency is hindered by the absence of a clear focus on superior commodities. This study aims to identify key commodities to support effective and sustainable regional development. The analysis integrates several methods, primarily Location Quotient (LQ), Shift-Share Analysis, and Growth-Share Analysis, to determine commodity competitiveness and growth potential. Supporting insights were also drawn from institutional, subsystem, and SWOT analyses. The findings highlight that the horticulture subsector, particularly pineapple, demonstrates strong regional specialization, competitive advantage, and consistent production growth. These characteristics position pineapple as a dominant and prospective commodity for agropolitan development in Subang Regency. Consequently, strategic planning efforts are recommended to prioritize the expansion and support of pineapple cultivation.